Genetic study of a family with affected members with Waardenburg syndrome type 4 without Hirschsprung disease - Moghadam, Mitra Sabetghadam; Rayat, Sima; Morovvati, Saeid (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Waardenburg syndrome (WS) is an autosomally inherited disorder with the most common state compounding pigmentary abnormality and sensorineural deafness. The rarest type of the disease is WS4 with the general characteristic discriminated from other types by the attendance of Hirschsprung disease (HD). Among the several genes, one of the causative genes in WS4 is endothelin 3 (EDN3) with both autosomal recessive and dominant inheritance. Aim. The intention of the present study is to report a pathogenic mutation as the genetic cause of WS in an Iranian family with four patients without any segregation criteria for the type of the disease. Material and methods. In order to detect of causing gene or genes related to the disease, Whole exome sequencing (WES) technique in proband’s sample was done. To confirm the detected mutation in proband and some family members with or without the disease direct sequencing of END3 gene was performed using Sanger method. Results. Pedigree analysis suggested segregation of WS as an autosomal recessive trait in the family. WES analysis suggested a gene (EDN3) related to WS type 4B. DNA sequencing confirmed a pathogenic missense mutation c.293C>T, p.T98M in EDN3 gene in all of the four patients. Conclusion. Determination of WS can usually be missed owing to the lack of some attributes in every sufferer and also conventional clinical variance, in spite of several affected members in a single family. So, Genetic counseling is pivotal for families with multiple members influenced. We detected c.293C>T, p.T98K mutation in EDN3 gene as a pathogenic variant which has been known as a likely pathogenic state in the American College of Medical Genetics and Genomics (ACMG) guidelines, despite one prior report. It will be helpful in genetic diagnosis of affected persons and increases the mutation spectrum of EDN3 gene.
Keywords: EDN3 gene; Waardenburg syndrome; WS4